RFID-enabled presence aware system (RPAS) - Haron, Nazleeni Samiha; Hasan, Mohd Hilmi; Mohd Ariffin, Mazeyanti; Patah Akhir, Emelia Akashah; Syadia Arina; Jusoff, Kamaruzaman (IDOSI Publications, 2011)
Presence is a person’s availability and willingness for communication at the time responses were sought from him or her. This piece of information is vital to people in need of immediate communication. By knowing one’s presence, the person can explore on meeting opportunities and perform decision making instantaneously. SMS, e-mail, shared calendar or instant messaging (IM) are the common methods to seek presence, but they impose some limitations that do not remedy the situation completely. As such, RFID-enabled Presence Aware System (RPAS) was proposed. The objective of the paper is to design and implement RPAS to enable automatic presence detection using RFID and make presence information sharable via web application. The study was conducted using six-phased structural development method. The user acceptance testing and the formal tests carried out revealed that the system was easy to use and useful. This study implies that automatic presence detection and shareable presence status will contribute to effective time management for personnel that indirectly gain the competitive strength for an organization. Future work includes integrating context-aware computing in RPAS for more intelligent presence detection system.